ANTIFUNGAL POTENTIAL OF LEAF EXTRACTS OF LEGUMINOUS TREES AGAINST SCLEROTIUM ROLFSII - Sana, Nighat; Shoaib, Amna; Javaid, Arshad (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Sclerotium rolfsii Sacc. is a destructive soil-borne plant pathogen that infects over 500 plant species and causes significant yield losses in many economically important plant species. Synthetic fungicides used to combat the menace also pollute the environment and cause health hazards. In order to search environmental friendly alternatives from natural resources, in the present study, methanolic extracts of three leguminous tree species namely Acacia nilotica (L.) Willd. ex Delile subsp. indica (Benth.) Brenan, Prosopis juliflora (Sw.) DC. and Albizia lebbeck (L.) Benth. were evaluated for their antifungal activity against S. rolfsii.Materials and Methods: Two hundred grams dried leaf material of each of the three test plant species were extracted with methanol for two weeks. After filtration, methanol was evaporated on a rotary evaporator. Malt extract broth was used to make various concentrations of the crude methanolic extracts and their antifungal potential was determined by comparing the fungal biomass in various treatments with control. Chemical composition of methanolic leaf extract of A. nilotica subsp. indica was determined through GC-MS analysis.Results: Methanolic leaf extract of A. nilotica subsp. indica showed the highest fungicidal activity. Fungal biomass was decreased by 17-55% due to various concentrations of this extract over control. Different concentrations of P. juliflora reduced fungal biomass by 3-52%. Fourteen compounds were identified in methanolic extract of A. nilotica subsp. indica. 9,12,15-octadecatrienoic acid, methyl ester, (Z,Z,Z,)- (16.59%) was the most abundant compound followed by 1-pentanol, 2 methyl-, acetate (14.80%); hexanedioic acid, dimethyl ester (13.10%) and cyclotriaconta- 1, 7, 16, 22-tetraone (10.28%).Conclusion: This study concludes that methanolic leaf extract of A. nilotica subsp. indica can be used for management of S. rolfsii.